Аналіз імунологічних показників та їх патогенетичних роль у розвитку запальних захворювань порожнини рота = Analysis of immunological parameters and their pathogenetic role in the development of inflammatory diseases of the oral cavity - Zalyubovska, O. I.; Tiupka, T. I.; Zlenko, V. V.; Avidzba, Yu. N.; Minaieva, A. O.; Bagmut, I. Yu. (Journal of Education, Health and Sport, 2016)
Zalyubovska O. I., Tiupka T. I., Zlenko V. V., Avidzba Yu. N., Minaieva A. O., Bagmut I. Yu. Аналіз імунологічних показників та їх патогенетичних роль у розвитку запальних захворювань порожнини рота = Analysis of immunological parameters and their pathogenetic role in the development of inflammatory diseases of the oral cavity Journal of Education, Health and Sport. 2016;6(10):616-624. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.189959 http://ojs.ukw.edu.pl/index.php/johs/article/view/4027 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК 616.314.18-002.4.-037-031.81-615.37 АНАЛІЗ ІМУНОЛОГІЧНИХ ПОКАЗНИКІВ ТА ЇХ ПАТОГЕНЕТИЧНА РОЛЬ У РОЗВИТКУ ЗАПАЛЬНИХ ЗАХВОРЮВАНЬ ПОРОЖНИНИ РОТА О. І. Залюбовська, Т. І. Тюпка, В. В. Зленко, Ю. Н. Авідзба, А. О. Мінаєва*, І. Ю. Багмут ** Харківський національний медичний університет *Національний фармацевтичний університет **Харківська медична академія післядипломної освіти Реферат Встановлено, що розвиток експериментального гінгівіту та пародонтиту у білих щурів супроводжується порушеннями як клітинної, так і гуморальної ланок імунної системи, і полягають у вірогідному зменшенні вмісту загальних зрілих Т-лімфоцитів (CD3+) та Т-лімфоцитів-хелперів (CD4+), збільшенні Т-супресорів (CD8+) та зниженні відносного вмісту В-лімфоцитів (СD20+). Застосування екзогенного мелатоніну при запальних захворюваннях пародонту призводить до нормалізації клітинної і гуморальної ланок імунітету експериментальних тварин. Ключові слова: запалення, гінгівіт, періодонтит, імунотерапія. Analysis of immunological parameters and their pathogenetic role in the development of inflammatory diseases of the oral cavity O. I. Zalyubovska, T. I. Tiupka, V. V. Zlenko, Yu. N. Avidzba, A. O. Minaieva *, I. Yu. Bagmut** Kharkiv National Medical University National University of Pharmacy, Kharkiv Kharkiv Medical Academy of Postgraduate Education Abstract It was established that the development of experimental gingivitis and periodontitis in white rats accompanied by disturbances both cellular and humoral immune system, and are as credible reduction of total mature T lymphocytes (CD3 +) and T-lymphocytes (CD4 +), increasing T suppressors (CD8 +) and decrease the relative content of B cells (CD20 +). The use of exogenous melatonin in inflammatory periodontal disease leads to normalization of cellular and humoral immunity experimental animals. Key words: inflammation, gingivitis, periodontitis, immunotherapy.